The Influence of Project Based Learning LKPD on Scientific Thinking Skills and Collaboration in Science Learning in Class V of Elementary School - Ummul Khaira; Yeni Erita; Desri Nora; Ulfia Rahmi; Padrius (Postgraduate, University of Mataram, 2025)
This research aims to measure the effectiveness of Student Worksheets (LKPD) based on Project Based Learning (PBL) in improving students' cooperation and scientific thinking skills in science subjects in elementary schools. Using a quasi-experimental design with a nonequivalent control group, this research involved 60 fifth grade students who were divided into an experimental group (using PBL-based LKPD) and a control group (using conventional methods). Instrument is a questionnaire to measure cooperation and a written test to measure scientific thinking abilities. The results of the analysis show that the average student collaboration score in the experimental group was 85.3, higher than the control group which only reached 78.4. The average score for scientific thinking ability in the experimental group reached 82.7, compared to 75.6 in the control group. Data analysis using the independent t test, after fulfilling the assumptions of normality and homogeneity of variance, showed statistically significant differences with a p value < 0.05. Results indicate that the use of PBL-based LKPD is more effective in increasing students' cooperation and scientific thinking abilities compared to conventional methods. This research suggests a wider application of PBL in science learning in elementary schools to optimize students' collaborative and scientific thinking skills.